The AMPA receptor antagonist perampanel suppresses epileptic activity in human focal cortical dysplasia. Issue 3 (11th May 2022) - Brito da Silva, Anderson; Pennifold, Jane; Henley, Ben; Chatterjee, Koustav; Bateman, David; Whittaker, Roger W.; Joshi, Abhijit; Kumar, Hrishikesh; Nicholson, Claire; Baker, Mark R.; Greenhill, Stuart D.; Walsh, Richard; et al.
Abstract: Focal cortical dysplasia (FCD) is one of the most common malformations causing refractory epilepsy. Dysregulation of glutamatergic systems plays a critical role in the hyperexcitability of dysplastic neurons in FCD lesions. The pharmacoresistant nature of epilepsy associated with FCD may be due to a lack of well‐tolerated and precise antiepileptic drugs that can target glutamate receptors. Here, for the first time in human FCD brain slices, we show that the established, noncompetitive α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor antagonist, perampanel has potent antiepileptic action. Moreover, we demonstrate that this effect is due to a reduction in burst firing behavior in human FCD microcircuits. These data support a potential role for the treatment of refractory epilepsy associated with FCD in human patients.